Peningkatan Prestasi Belajar Matematika Melalui Model Kooperatif Tipe Group Investigation pada Materi Transpormasi Geometri Terhadap Siswa Kelas IX-1 MTsS Kampung Beusa - Rizayanti (Jurnal Aktual Pendidikan Indonesia, 2022)
Monthly and annual plans. The preparation contains the teaching objectives, the subject to be taught, the methods, materials, teaching aids and evaluation techniques used, therefore the teacher must understand correctly the objectives to be achieved, how to choose, determine and use teaching aids, how to make tests. and knowledge of evaluation tools. The research objectives to be obtained are: a) To reveal the application of Group Investigation Cooperative Type to mathematics learning outcomes. b) To reveal Cooperative Type Group Investigation on motivation to learn mathematics. This study used two rounds of action research. Each round consists of four stages: design, learning activities and observations, reflection and revision. The target of this research was students of class IX-1 MTsS Kampung Beusa, East Aceh District. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that student achievement increased from cycle I to cycle II, namely, cycle I (64.29%), cycle II (90.47%). The conclusion from this study is that the application of Cooperative Group Investigation Type can have a positive effect on student achievement and motivation in class IX-1 MTsS Kampung Beusa and this learning model can be used as an alternative to learning mathematics.